Redemption - Baldacci, David (Baldacci, David. Amos Decker series., 2019)
Amos Decker and his FBI partner Alex Jamison are visiting his hometown of Burlington, Ohio, when he's approached by an unfamiliar man. But he instantly recognizes the man's name: Meryl Hawkins. He's the first person Decker ever arrested for murder back when he was a young detective. Though a dozen years in prison have left Hawkins unrecognizably aged and terminally ill, one thing hasn't changed: He maintains he never committed the murders. Could it be possible that Decker made a mistake all those years ago? As he starts digging into the old case, Decker finds a startling connection to a new crime that he may be able to prevent, if only he can put the pieces together quickly enough.